UPAYA PENINGKATAN PARTISIPASI KELUARGA DALAM RANGKA WAJIB BELAJAR 9 TAHUN DI SMPN 1 SALATIGA - Rosyulianty, Kania; Aswandi, Aswandi; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe nine-year compulsory program programmed by the government is a continuation of previous educational programs. The goal is to provide the basic right for the community to obtain educational services. To achieve that goal one of the factors that determine its success is the presence of family participation on education. Related to that, the researcher conducted a study at SMP Negeri 1 Salatiga Kabupaten Sambas. Research questions are directed to: How aspirations, expectation, planning and implementation, as well as barriers to the program of increasing family participation in the framework of 9-year compulsory education at SMP Negeri 1 Salatiga Kabupaten Sambas. To express the question the researcher uses a qualitative research approach type of case study research. To gather data and information from informants, researchers used observation, interviews, and document studies in the process of collecting research data. The results revealed that; The aspirations of the family are generally good, the expectation / success of the essence is very high, the planning is done early in the inhibiting factors such as low economic condition of the parents and the pattern of life that has not changed. Kata kunci: Partisipasi, Pendidikan, Wajib Belajar 9 Tahun